Nebulization as a delivery method for mAbs in respiratory diseases. (June 2014) - Respaud, Renaud; Vecellio, Laurent; Diot, Patrice; Heuzé-Vourc'h, Nathalie
<x xml:space="preserve">Abstract</x> Introduction: The pulmonary route is not invasive and can be used to target drugs directly to the lungs, limiting the exposure of secondary organs. It is, thus, an attractive alternative to the intravenous route, for the delivery of mAbs, which display limited transfer from blood into the lungs. Areas covered: This review provides an overview of the pharmacological properties of antibody-based treatments, describes those for respiratory diseases and discusses preclinical/clinical results of aerosolized antibody-based therapeutics. The advantages and limitations of aerosol devices and the formulation for the administration of aerosolized mAbs are also detailed. Expert opinion: Overall, the inhalation of mAbs for therapeutic purposes is both appropriate and feasible. The size and structure of the biotherapeutic molecule are important properties to be taken into account when trying to achieve long-term retention. Mesh nebulizers currently appear to be the most appropriate devices for the safe delivery of large amounts of active mAb into the lungs. mAbs should be formulated so as to prevent their degradation and possible immunogenicity. General guidelines can be given for mAb aerosolization, but the formulation and device combination should be adapted for each therapeutic and clinical application.